Successful high-performance ice hockey coaches` intermission routines and situational factors that guide implementation - Allain, J.; Bloom, G. A.; Gilbert, W. D. (The Sport Psychologist, 2018)
Competitions in many team sports include short breaks (e.g., intermissions, halftime) where coaches have a unique opportunity to make tactical adjustments and communicate with athletes as a group. Although these breaks are significant coaching moments, very little is known about what successful coaches do during this time. The purpose of this study was to examine intermission routines and knowledge of highly experienced and successful National Collegiate Athletic Association (NCAA) ice hockey coaches. A thematic analysis was used to analyze semistructured and stimulated-recall interview data. Results revealed that coaching during intermissions was a continuous process influenced by the coaches` history and personal characteristics. Drawing on these factors, the coaches created an intermission routine that guided them as they analyzed unpredictable situational factors such as their team`s performance and the athletes` emotional state. Overall, the results offer a rare glimpse into the intermission strategies of successful coaches in a high-performance setting.